Pengaruh Disiplin Kerja dan Kompetensi Profesional Terhadap Kinerja Guru SMP dan SMA Muhammadiyah Matraman dalam Situasi Pandemi Covid-19 - Siti Nurjanah; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to analyze the effect of work discipline and professional competence on the performance of Muhamadiyah Matraman Middle and High School teachers in the Covid-19 pandemic situation. This study uses a quantitative approach. Methods of data collection using a questionnaire. The research method uses multiple analysis regression. The population in this research is teachers who work in SMP and SMA Muhammadiyah Matraman. The sampling technique used in this study was non-probability sampling and data analysis was processed using the SPSS 20 application. The results of hypothesis testing showed that the work discipline variable had no effect on teacher performance. professional competence variables affect teacher performance and work discipline and professional competence variables have an influence on teacher performance.